Strategi Pembelajaran Karakter Anak Usia Dini model Daring di masa Pandemic Covid-19 (Studi kasus pada PAUD Anak Kita Preschool Samarinda) - Heppy Liana (Manajemen Pendidikan Program Doktor, 2021)
This study aims to describe how the strategy of early childhood educators in carryingout early childhood character learning during the coronavirus19 disease 19 when learningactivities are carried out at home. The researcher used a qualitative descriptive approach with acase study method to gain an understanding of the strategies of early childhood educators inimplementing early childhood character learning. Data collection techniques used are interviewsand documentation. The data collected was then analyzed using an interactive model with dataanalysis steps, namely data reduction, data presentation, conclusion drawing, and verification.The results showed that there were changes in learning activities carried out before and duringthe covid-19 pandemic, First: the strategy of implementing learning through collaborationbetween educators and parents by sharing tasks, namely, educators as planners and assessment oflearning outcomes while for the task of implementing learning carried out by parents, so thatparents become partners during learning activities at home, including the task of parents is toprepare tools and play materials that are lent by the school and added to the tools and playingmaterials that are around the house, accompanying children, motivating children anddocumenting activities that children do then send the documentation to the homeroom teacher tobe analyzed and reported as a child development report carried out PAUD educators are assistedby parents at home, secondly: Educator's Strategy in instilling character values through learningactivities from At home during the COVID-19 pandemic, there are 11 character values that canbe developed in Anak Kita Preschool, including: 1) Religious, 2) Honest, 3) Tolerance, 4)Discipline, 5) Hard work, 6) creative, 7) independent, 8) curious, 8) friendly/communicative, 9)likes to read, 10) cares about the environment, and 11) is responsible. These eleven charactersvalues are developed through stimulation, storytelling, facilitation and good habituation fromadults, namely educators and parents and are evaluated based on six aspects of childdevelopment.